2022
DOI: 10.1038/s41467-022-34960-9
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric rescue of catalytically impaired ATP phosphoribosyltransferase variants links protein dynamics to active-site electrostatic preorganisation

Abstract: ATP phosphoribosyltransferase catalyses the first step of histidine biosynthesis and is controlled via a complex allosteric mechanism where the regulatory protein HisZ enhances catalysis by the catalytic protein HisGS while mediating allosteric inhibition by histidine. Activation by HisZ was proposed to position HisGS Arg56 to stabilise departure of the pyrophosphate leaving group. Here we report active-site mutants of HisGS with impaired reaction chemistry which can be allosterically restored by HisZ despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…48 ■ DISCUSSION Dissecting the kinetics of allosteric regulation of enzymes is crucial to understand which steps along the reaction cycle are responding to the allosteric effector. 26,28,30,49 In addition, recent studies have highlighted the effect temperature can exert on allosteric regulation, 50,51 and how dynamic allostery responds to temperature changes to drive temperature adaptation. 49 As an example, in thermophilic T. maritima imidazole glycerol phosphate synthase (IGPS), a V-type heterodimeric allosteric enzyme catalyzing the fifth step of histidine biosynthesis, allosteric activation by N′-[5′phosphoribulosyl)formimino]-5-aminoimidazole-4-carboxamide-ribonucleotide leads to 4200-fold increase in k cat at 30 °C, but only 65-fold at 70 °C (near T. maritima's natural growth temperature).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…48 ■ DISCUSSION Dissecting the kinetics of allosteric regulation of enzymes is crucial to understand which steps along the reaction cycle are responding to the allosteric effector. 26,28,30,49 In addition, recent studies have highlighted the effect temperature can exert on allosteric regulation, 50,51 and how dynamic allostery responds to temperature changes to drive temperature adaptation. 49 As an example, in thermophilic T. maritima imidazole glycerol phosphate synthase (IGPS), a V-type heterodimeric allosteric enzyme catalyzing the fifth step of histidine biosynthesis, allosteric activation by N′-[5′phosphoribulosyl)formimino]-5-aminoimidazole-4-carboxamide-ribonucleotide leads to 4200-fold increase in k cat at 30 °C, but only 65-fold at 70 °C (near T. maritima's natural growth temperature).…”
Section: ■ Resultsmentioning
confidence: 99%
“…22 A coldadapted bacterium also from the Moraxellaceae family, Psychrobacter arcticus, possesses an orthologous short-form ATPPRT whose HisG S and HisZ subunits share 69% and 43% amino acid sequence identity, respectively, with AbHisG S and AbHisZ; despite these similarities, P. arcticus ATPPRT follows a strictly ordered mechanism with PRPP binding to the free enzyme. 18,25 An in-depth kinetic investigation of allosteric regulation of catalysis is necessary to uncover fundamental aspects of this widespread phenomenon in protein biochemistry 27,28 and to offer additional opportunities for drug design. 22,29 The common classification of allosteric control into K-type (where the Michaelis constant is affected) and V-type (where k cat is affected) systems, 27 while useful at a macroscopic level, does not provide insight into the microscopic steps along the enzymatic reaction being directly perturbed by the allosteric effector.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, generated inorganic phosphate from the subsequent hydrolysis step is quantified over time via fluorescence indirectly using a coupled assay, making it difficult to determine whether the second-shell mutation effects were largely on the chemical step or substrate binding or which functional states are most perturbed. Similarly, previous computational studies of distal mutation effects rarely examined all the essential steps in the catalytic cycle; they either focused on perturbation of the chemical step or residues that exhibit motional coupling with binding or conformational equilibria in the active site. ,,, To establish the contributions of second-shell residues, it is necessary to explicitly analyze multiple enzymatic states, which in turn requires striking the proper balance between accuracy in energetics and efficiency in conformational sampling. Meeting such requirements is particularly challenging for metalloenzymes such as PafA, since metal–ligand interactions generally require sophisticated computational models to properly treat ligand polarization, coordination geometry and flexibility, and metal–ligand charge transfers. , …”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been focused on naturally evolved and designed enzymes to establish the physical principles and molecular features that govern their catalytic properties. One common observation is that residues beyond the first coordination shell of the substrate can often make considerable cumulative contributions to the catalytic efficiency, specificity, and substrate scope. Stimulated by these observations, numerous experimental and computational studies aimed to reveal the precise molecular mechanism of the notable mutation effects of distal residues to enzyme catalysis. ,, A general consideration is that due to the energetic coupling among residues in the enzyme, local changes associated with remote mutations propagate into the active site to impact conformational equilibria of key catalytic residues or electrostatics therein. For example, a combination of mutagenesis, kinetic, NMR, and computational studies of the dihydrofolate reductase supported the notion of a coupled network of interactions between residues that are spatially separated in the protein structure, leading to considerable contributions of distal residues to the hydride donor–acceptor distance distributions and therefore hydride transfer kinetics. , Moreover, NMR and extensive molecular dynamics (MD) simulations have shown that in many cases, distal mutations lead to a redistribution of pre-existing conformational states that favor a particular catalytic activity , or alter the conformational dynamics of essential structural motifs that gate the active site pocket and therefore substrate binding/product dissociation. , Building on these mechanistic insights, considerable progress has also been made to identify the location of remote regions that might couple strongly with the active site, which may help reduce the cost of powerful yet time-consuming enzyme engineering approaches such as random saturation mutagenesis and directed evolution , by providing decent starting points. Prominent examples include using chemical shift perturbations to locate sites that respond to binding of inhibitors, using correlation-based analysis of molecular dynamics trajectories to locate residues allosterically coupled to the active site, and using flexibility profiles to identify sites that dictate functionally relevant dynamics of enzymes.…”
Section: Introductionmentioning
confidence: 99%